Note sur les apports de Sismondi à la théorie classique - Arena, Richard (L'Actualité économique, 1981)
ABSTRACTThe topic of the paper is to estimate the importance of the contribution of Sismondi's economic analysis to the classical economic theory. To do this, the theoretical framework and the main concepts of the latter approach are first described. Three main themes allow us to distinguish the classical theory between the other ones: its conception of time and economic evolution, its apprehension of the different categories of economic agents and its analysis of wealth and prices. The paper deals with each theme and analyses its contents and place in Sismondi's work. The study of the relation between time and economie evolution allows the introduction of uncertainty in the perfect foresight classical scheme. As far as the notion of economic agent is concerned, Sismondi specified the classical conception of social classes in capitalism. Finally, in his treatment of wealth and prices, Sismondi emphasizes the importance of market forces and gluts. The conclusions of the paper are the following: Sismondi's approach and classical analysis cannot be interpreted as inconsistent; moreover, Sismondi can be considered both as Ricardo's successor and as Keynes' predecessor.